The Role of Water Supply in the Architecture of Safavid Royal Mansions (Chehelsotoon Mansion) Architecture with an Emphasis on the Role of Water a d Nature - kaveh farhadi; Mostafa Taghizadeh (Dānishhā-yi būmī-i Īrān, 2019)
. In this paper, the present researchers tried to review the elements and components existing between the Safavid era and the principles and architectural techniques of that period; in this sense, purity and cleanliness are also introduced along with the concepts of hidden aspects and finding the water architecture. However, in order to solve the critical problems in the water sphere, the unique features of our culture and beliefs are of particular importance to Iranians at that time. Therefore, in this paper, emphasizing the ancient symbols and images that their secret, according to Jung, is unconscious, we emphasize the symbols and beliefs in the context of the culture of the Iranian society, whose various forms have emerged, especially in the ritual of purity and the purification forms allegorical and metaphorical forms in the form of arts or belief beliefs. These forms, which are rooted in mythological beliefs (also the myths), have been a religious practice, and in the structures of Islamic art, the sanctity and purification of the window of this form have entered the arena of art with the appearance of water, and in the streams of beliefs and signs and symbols. The architecture of Isfahan school is fertilized with the help of its knowledge of time, and neglecting it causes the decline and decline of the Safavid era, and its effects appear to continue in the subsequent periods.